Required educational transformations in the College of (C.E.C.S) at (I.M.B.S) University considering the corona pandemic from the point of view of the faculty Members - Khalid Al-Dahmash (International Journal of Instructional Technology and Educational Studies)
This study aimed at identifying the difficulties that face all male and female faculty members’ students at the College of Continuing Education and Community Service (C.E.C.S) at Imam Muhammad bin Saud Islamic (I.M.B.S) University in light of the Corona pandemic, hence, to achieve the college’s required educational transformations. The researcher used the most scientific method known as the descriptive approach (survey) which is most suitable for the nature of the current study, using the questionnaire as a tool for it, that has been judged and verified for its validity and reliability.The results of the study showed that most of the study members agreed that the faculty members face twelve difficulties, most notably in respect to their curricula, qualification, and training. It also showed that most of the study members agreed that the faculty members face fifteen difficulties, most prominent of which is the reflection of the psychological state, and their frequent inquiries about the technical aspect plus the self-learning difficulties they face. The study recommended the need to pay attention to developing curricula and electronic courses, qualifying and training faculty members, in addition to supporting the gradual transformation process in education from the traditional to the default mode.